Pemberdayaan UMKM Gerabah Melalui Pembentukan Komunitas Pra-Koperasi Di Kabupaten Ponorogo - Sri Umi Mintarti; Dian Rachmawati Ghozali; Syahrul Munir; Yogi Dwi Satrio (Universitas Lancang Kuning, 2020)
Problems that occur in clay craftsmen in Plancungan Village, Ngloning Village and Gombang Village, Slahung District, Ponorogo Regency include lack of capital, lack of marketing networks and low product innovation, and lack of regeneration in this business. So as to overcome these problems is done by providing training and the formation of pre-cooperatives for the craftsmen. The purpose of this service is to improve the quality of human resources and promote the existence of earthenware vessels. Community service activities are carried out by forming a pre-cooperative community in order to facilitate the availability of capital for craftsmen. In addition, there will also be some marketing training and training to increase product innovation so that it has added value and innovation that is in line with the needs of the times. Both of these trainings were carried out by marketing practitioners and from the industry department and cooperatives of Ponorogo Regency.